IP Receptor Agonist-Induced DNA Synthesis and Proliferation in Primary Cultures of Adult Rat Hepatocytes: the Involvement of Endogenous Transforming Growth Factor-α - Mitsutoshi Kimura; Hiroshi Okamoto; Hideshi Natsume; Masahiko Ogihara (Elsevier, 2009)
To elucidate the mechanism of action of prostaglandin I2 (PGI2) and carbaprostacyclin, we studied their effect on DNA synthesis and proliferation in primary cultures of adult rat hepatocytes. Hepatocyte parenchymal cells, maintained in a serum-free, defined medium, synthesized DNA and proliferated in the presence of PGI2 or carbaprostacyclin in a time- and dose-dependent manner. PGI2 was less potent than carbaprostacyclin in stimulating hepatocyte mitogenesis. These effects of PGI2 and carbaprostacyclin were abolished by treatment with a specific IP-receptor antagonist, CAY10441 (10−9 - 10−7 M). Hepatocyte mitogenesis induced by the IP-receptor agonists was almost completely blocked by specific inhibitors of growth-related signal transducers such as AG1478 (5 × 10−7 M), LY294002 (10−7 M), PD98059 (10−6 M), and rapamycin (10 ng/ml). In addition, PGI2 or carbaprostacyclin significantly increased the kinase activity of a (p175 kDa) receptor tyrosine kinase and the phosphorylation of extracellular signal-regulated kinase (ERK) 2. Addition of a monoclonal antibody against transforming growth factor (TGF)-α, but not insulin-like growth factor-I, to the culture dose-dependently inhibited the PGI2-or carbaprostacyclin-induced hepatocyte mitogenesis. Furthermore, treatment with the IP-receptor agonists significantly increased the secretion of TGF-α to the culture medium. These results indicate that the IP receptor agonist-induced hepatocyte mitogenesis is mediated by autocrine secretion of TGF-α followed by activation of a receptor tyrosine kinase / ERK pathway. Keywords:: DNA synthesis, proliferation (cultured hepatocyte), prostaglandin I2, transforming growth factor-α, signal transduction